2009
DOI: 10.1007/s00239-009-9227-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Heteroplasmy in the Human Mitochondrial DNA Control Region: A Synthesis of Observations from More Than 5000 Global Population Samples

Abstract: Instances of point and length heteroplasmy in the mitochondrial DNA control region were compiled and analyzed from over 5,000 global human population samples. These data represent observations from a large and broad population sample, representing nearly 20 global populations. As expected, length heteroplasmy was frequently observed in the HVI, HVII and HVIII C-stretches. Length heteroplasmy was also observed in the AC dinucleotide repeat region, as well as other locations. Point heteroplasmy was detected in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
111
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 47 publications
15
111
3
2
Order By: Relevance
“…In addition, length heteroplasmy found in this region of the HVS-I reproduced a complex DGGE pattern. In our study, individuals with HVS-I motif 126-163-186-189-294 (haplogroup T1) resulting in a string of seven cytosines did not exhibit length heteroplasmy, thereby supporting the hypothesis that eight cytosines is likely the critical number (Melton 2004;Chen et al, 2009;Irwin et al, 2009;Forster et al, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…In addition, length heteroplasmy found in this region of the HVS-I reproduced a complex DGGE pattern. In our study, individuals with HVS-I motif 126-163-186-189-294 (haplogroup T1) resulting in a string of seven cytosines did not exhibit length heteroplasmy, thereby supporting the hypothesis that eight cytosines is likely the critical number (Melton 2004;Chen et al, 2009;Irwin et al, 2009;Forster et al, 2010).…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…We found seven point heteroplasmic transitions in a total of six samples (499R, 16284R twice, 204Y three times) concurring with heteroplasmic sites observed in more than 5,000 global population samples [23] whereas one instance of heteroplasmy (16327Y) has not been reported there.…”
Section: Point Heteroplasmysupporting
confidence: 79%
“…Before the application of next-generation sequencing (NGS) technologies, most studies focused on the mtDNA control region and revealed that 6∼11.6% of the population carry heteroplasmy in this region (9)(10)(11). The advent of NGS technologies enables the inquiry of mitochondrial heteroplasmy at the genome-wide scale.…”
mentioning
confidence: 99%